The Effectiveness of Learning Guidance Service with Animation in Improving Students’ Learning Motivation - Mufidah, Elia Firda; Mudhar, Mudhar; Wahyuni, Lilis (Universitas Ahmad Dahlan, 2022)
This work was driven by Class VIII-G students’ poor learning motivation During the Covid-19 pandemic. It aims to find out the effectiveness of animation media in enhancing students’ learning motivation. To this end, a qualitative pre-experimental study with a pretest-posttest design was applied. It involved twenty-six students from class VIII-G as participants, recruited using a purposive sampling technique. The data were collected using a learning motivation scale and structured interview and analyzed using a t-test. The analysis result showed a sig. value (2-tailed) of 0.00 (< 0.05), indicating that Ho was rejected and Ha was accepted. In other words, animation media is effective in enhancing students’ learning motivation in Class VIII-G of SMP PGRI 1 Buduran. This result could be used as a reference for improving students’ learning motivation using animation.